Nickel-Catalyzed Hydrodeoxygenation of Aryl Sulfamates with Alcohols as Mild Reducing Agents - Matsuo, Kasumi; Kuriyama, Masami; Yamamoto, Kosuke; Demizu, Yosuke; Nishida, Koyo; Onomura, Osamu (Synthesis, 2021)
The nickel-catalyzed hydrodeoxygenation of aryl sulfamates has been developed with alcohols as mild reductants. A variety of functional groups and heterocycles were tolerated in this reaction system to give the desired products in high yields. In addition, the gram-scale process and stepwise cine-substitution were also achieved with high efficiency.
Keywords: nickel; reduction; hydrodeoxygenation; sulfamate; alcohol